1989
DOI: 10.1038/bjc.1989.255
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpromazine reduces UV-induced squamous cell carcinogenesis in hairless mice and enhances UV-induced DNA damage in cultured cells

Abstract: Summary Administration of the photoactivable compound chlorpromazine (CPZ) to SKH-1 hairless mice via their drinking water (CPZ, 0.01%) significantly reduced the rates of accumulation and yields of squamous cell carcinomas induced by long-term repeated exposures of these animals to solar UV radiation. This protective effect of CPZ was partially reversed in mice given a single injection of ethyl nitrosourea at birth. In in vitro studies, the presence of CPZ (0.2 mM) in mammalian cell cultures enhanced the yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…On the contrary, derivatives containing a hydrogen or a trifluoromethyl group instead of chlorine in position 2 of the phenothiazinic ring, were not photogenotoxic. Two photocarcinogenicity in vivo studies with CPZ have yielded contradictory results: Peak et al [148] observed a strong reduction of UV induced skin tumor formation while Kelly et al [140] found a strong enhancement of UV induced skin carcinogenesis. Both laboratories used hairless SKH mice and employed lamps with broad emission spectra including visible light.…”
Section: Uva-induced Genetic Effects Of Phenothiazinesmentioning
confidence: 97%
See 1 more Smart Citation
“…On the contrary, derivatives containing a hydrogen or a trifluoromethyl group instead of chlorine in position 2 of the phenothiazinic ring, were not photogenotoxic. Two photocarcinogenicity in vivo studies with CPZ have yielded contradictory results: Peak et al [148] observed a strong reduction of UV induced skin tumor formation while Kelly et al [140] found a strong enhancement of UV induced skin carcinogenesis. Both laboratories used hairless SKH mice and employed lamps with broad emission spectra including visible light.…”
Section: Uva-induced Genetic Effects Of Phenothiazinesmentioning
confidence: 97%
“…DNA breakage alkaline elution [140] and Comet assay [141] give further evidence of the genotoxicity actions of the compounds. As far as detailed in the reports the compounds and the cells were irradiated concomitantly.…”
Section: Uva-induced Genetic Effects Of Phenothiazinesmentioning
confidence: 99%
“…1975;SHENOY and GOPALAKRISHNA 1978;GEORGE et al 1980;GEORGE and SINGH 1984). PEAK et al (1989) reported that CPZ treatment increased the frequency of DNA strand breaks induced by UV radiation in cultured mammalian cells. Similarly, CPZ has also been found to enhance the damage caused by alkylating agents and caffeine (COHEN 1973(COHEN , 1975LIALIARIS et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…There are no reports of an increased risk of skin cancer due to the phototoxicity of CPZ [ 38 ]. Instead, it may suppress UV-carcinogenesis [ 167 , 168 ]. It is hypothesized that CPZ may act as an antioxidant and neutralize the potential harmful effects of the radicals on the DNA, thus limiting genotoxicity [ 167 , 168 ].…”
Section: Phototoxic Drugsmentioning
confidence: 99%
“…Instead, it may suppress UV-carcinogenesis [ 167 , 168 ]. It is hypothesized that CPZ may act as an antioxidant and neutralize the potential harmful effects of the radicals on the DNA, thus limiting genotoxicity [ 167 , 168 ]. Another possible mechanism is that CPZ may increase the activity of DNA repair or increase immune surveillance against UV-induced skin cancers [ 168 ].…”
Section: Phototoxic Drugsmentioning
confidence: 99%